Reconsidering the Death Penalty for Bribery in Law Enforcement to Prevent and Eradicate Corruption in Indonesia - Ridwan, Ridwan; Setiadi, Edi; Sambas, Nandang; Kartika, Arie; Anditya, Ariesta Wibisono (Faculty of Law, Jambi University, 2025)
Corruption is classified as an extraordinary crime due to its destructive impact on state administration, economic development, and public trust. Among the various forms of corruption in Indonesia, bribery constitutes the most fundamental and systemic offense, serving as the primary mechanism through which corruption is initiated, maintained, and normalized within public institutions. Within the justice system, bribery in law enforcement represents one of the most dangerous and corrosive forms of corruption, as it directly undermines the integrity of investigations, prosecutions, and judicial decisions. For this reason, extraordinary legal measures – including the death penalty – can serve as an alternative means to address severe bribery offenses. Nevertheless, its application in Indonesia faces legal challenges, mainly due to the shortcomings of the formulation of the death penalty provisions in the current Law on the Eradication of Corruption Crimes. Comparing with neighbouring countries concerning legal provisions for bribery, the author will assess how the reformulation or reconstruction of death penalty provisions could enhance the deterrent effect on corrupt officials in Indonesia. This study demonstrates that, despite ongoing debates over its implementation, the death penalty for bribery takers in Indonesia has a sound legal and rational foundation. Within law enforcement, it could strengthen the decisiveness of existing regulations and enhance their deterrent effect against such practices